Perception of Brazilians on death with dignity - Lins, Cynthia de Freitas Melo (2018)
Objectives: This research aimed to investigate the concept of dignified death for the Brazilian population. Method: An exploratory, national survey, quantitative study was carried out. An inadvertent non-probabilistic sample of convenience was made up of 412 Brazilians who answered the "Scale of perception of worthy death", whose data were analyzed through descriptive and bivariate statistics using the statistical package SPSS (Statistical Package for Social Science) for Windows version 22. Results: It was possible to verify that decent death implies, in order of priority, a good relationship with the family (M = 5.99; SD = 0.73), maintenance of hope and pleasure (M = 5.88; SD = 0.85), good relation with the professional health team (M = 5.46; SD = 1.00), not to be a burden to the others (M = 5.38; SD = 1.09), to have physical and cognitive control (M = 4.69; SD = 0.92) and control of the future (M = 4.57; SD = 1.14). Conclusions: The concept of good death is broad and its understanding provides for the strengthening of procedures related to "dignified death".